Impact of Body Composition on the Quality of Life of Premenopausal Patients with Early Stage Breast Cancer During Chemotherapy - Mirjana Pavlović Mavić; Robert Šeparović; Ljubica Vazdar; Ana Tečić Vuger; Marija Banović (Acta Clinica Croatica, 2022)
Body composition has been studied relatively recently as part of oncology trials in different types of tumors. There are numerous studies that define the impact of chemotherapy side effects on the quality of life (QoL) of breast cancer patients, however, there are few studies that analyze the impact of body composition on the QoL of premenopausal patients in the course of cytotoxic treatment. The study was performed on a sample of premenopausal patients treated with neoadjuvant or adjuvant AC chemotherapy for early-stage breast cancer at Day Hospital of the Department of Medical Oncology, University Hospital for Tumors in Zagreb. The study included 68 patients, median age 46.6 years. Analysis of the QoL questionnaires and their association with body composition indicated several interesting results. At the beginning of treatment, most pronounced was the connection between body composition and physical and sexual functioning and hair loss, while in subsequent treatment cycles the effect on other QoL subdomains, in particular fatigue and diarrhea, was more pronounced. In conclusion, we found body composition to have a significant impact on certain QoL subdomains during treatment.